Evaluation of Bread Making Performance of Some Wheat Flour Brands Available in Nigerian Markets as Affected by Cassava or Sweet Potato Flour Inclusion - Agbara, Gervase Ikechukwu; Ishira, Iliya; Kassum, Litini Afodia; Lawan, Hadiza Kubura (Journal of Food Technology Research, 2020)
The study examined the baking potential of wheat flour brands available in Nigerian markets and their performance in composite flour bread. Three flour brands were identified and selected based on availability and popularity: Dangote (DG) Bread flour, Golden penny (GP) Prime, and Honeywell(HW) Bakers Delight. Cassava (CV) and Sweet Potato (SP) flours were separately blended with each of the selected wheat flour brands in a ratio of 80:20 to obtain six formulations code named: DG, GP, HW, DGCV, DGSP, GPCV, GPSP, HWCV, HWSP. Breads were produced using AACC straight dough method. Physicochemical and sensory properties of the flours/flour blends were evaluated using approved procedures. The moisture, crude protein, crude fat, total ash, crude fibre and carbohydrate contents of the wheat and root flours were: 5.35-10.10%, 5.78-14.52%,1.79-3.15%, 0.80-2.59%, 1.77-3.15% and 70.83-81.16% respectively. GP flour had significant higher dry gluten (19.00%), water absorption capacity (2.0ml/g) and HW flour had the highest thoroughs (95%) through 212μm sieve followed by Sweet potato (92.50%) yet none met the Codex Alimentarius standard for wheat flour particle size. The specific volumes of the wheat breads varied significantly (p<0.05) from 2.55-3.28ml/g with GP leading, although DG had though had the highest absolute volume, those of composite flour bread (2.16-2.48ml/g) were lower and GP and HW flours produced better composite flour bread with cassava in terms of specific volume. The sensory attributes of GP and HW wheat breads were rated higher which also reflected in higher scores for GPCV and HWCV breads. This study has demonstrated that GP brand of wheat flour had superior bread baking performance either alone or in a blend with 20% cassava flour. It is recommended that further study be carried out involving other brands of wheat flour and other indicators of wheat flour quality.